(untitled) (Physical Education, Health and Social Sciences, 2025)
Background: Frozen shoulder a musculoskeletal disorder affecting 2-5% population cause pain with restriction of shoulder ranges and functional status Gong’s mobilization a manual therapy which shows promise in managing frozen shoulder through improved ROM and pain relief. Objective: The aim was to examines the treatment success of Gong’s mobilization for frozen shoulder cases by assessing its results against traditional physiotherapy approaches. Methodology: Total thirteen randomized controlled trials (RCTs) and pilot study about Gong’s mobilization in PubMed and PEDro and the Cochrane Library databases between the years 2000 and 2025 were included. The studies included on the basis of defined inclusion criteria. The Physiotherapy Evidence Database Scale (PEDro) scale used for assessment of studies qualities. Results: A total of 150 articles were screened in which 13 experiments comprising 12 RCTs along with a single experimental pilot study that studied 389 participants. The results demonstrated that Gong’s mobilization technique led to noteworthy improvements in pain ratings measured by VAS/NPRS scores and functional test results such as SPADI and Shoulder Constant Score as well as physical movement outcomes in flexion, abduction and external rotation. Conclusion: Gong’s mobilization technique produces significant functional and ROM and pain reduction benefits for patients with frozen shoulder. Additional high-quality research that utilizes large sample sizes together with standardization of procedures will be required.